Identification of Arcobacter in children and adult feces with/without diarrhea, and in animal reservoirs - Zerpa Larrauri, Rito (2014)
Introduction: Microorganisms of the genre Arcobacter considered emerging zoonotic pathogens are morphologically similar to Campylobacter. Reports of Arcobacteras as etiologic agent of diarrhea in humans in Latin America are scarce. In Peru its isolation in feces of humans or animals has not been reported. Objectives: To determine the prevalence of Arcobacter in feces of children and adults with/without diarrhea and in animals: birds, cattle, pigs, fish and seafood. Design: Cross-sectional study. Setting: Institute of Tropical Medicine Daniel A. Carrion, Universidad Nacional Mayor de San Marcos; National Institute of Child Health; Maternal and Child San Bartolome Institute; and Arzobispo Loayza Hospital. Biologic material: Bacterial isolates from stool samples of humans and animals. Interventions: Active search of Arcobacter sp. in human and animal feces, from July to October 2011. Main outcome measures: Prevalence of Arcobacter in feces. Results: Arcobacter sp. was found in samples from children with diarrhea (2/100), but not in those without diarrhea (0/97). In samples of adults with diarrhea (52) and without diarrhea (180), only one sample was isolated from a subject without diarrhea. Among animals, species with higher prevalence of Arcobacter sp were cattle (25%) and swine (29.2%). Among marine species, the two seafood species studied showed high prevalence: choro 24% (12/50) and prawns 22% (11/50). Conclusions: Arcobacter is a zoonotic germ potentially pathogenic to humans, particularly in children. Animal species used for human consumption should be studied systematically. It is important to perform studies in relation to ecological aspects, their behavior against antimicrobials and its transmissibility to humans.